TiO2 micro-nano-hybrid surface to alleviate biological aging of UV-photofunctionalized titanium - Iwasa F (Dove Medical Press, 2011)
Fuminori Iwasa1, Naoki Tsukimura1, Yoshihiko Sugita1, Rajita Kodali Kanuru1, Katsutoshi Kubo1, Hafiz Hasnain1, Wael Att1,2, Takahiro Ogawa11Laboratory of Bone and Implant Sciences (LBIS), The Weintraub Center for Reconstructive Biotechnology, Division of Advanced Prosthodontics, Biomaterials and Hospital Dentistry, UCLA School of Dentistry, Los Angeles, CA, USA; 2Department of Prosthodontics, Dental School, Albert-Ludwigs University, Freiburg, GermanyAbstract: Bioactivity and osteoconductivity of titanium degrade over time after surface processing. This time-dependent degradation is substantial and defined as the biological aging of titanium. UV treatment has shown to reactivate the aged surfaces, a process known as photofunctionalization. This study determined whether there is a difference in the behavior of biological aging for titanium with micro-nano-hybrid topography and titanium with microtopography alone, following functionalization. Titanium disks were acid etched to create micropits on the surface. Micro-nano-hybrid surfaces were created by depositioning 300-nm diameter TiO2 nodules onto the micropits using a previously established self-assembly protocol. These disks were stored for 8 weeks in the dark to allow sufficient aging, then treated with UV light for 48 hours. Rat bone marrow–derived osteoblasts were cultured on fresh disks (immediately after UV treatment), 3-day-old disks (disks stored for 3 days after UV treatment), and 7-day-old disks. The rates of cell attachment, spread, proliferation, and levels of alkaline phosphatase activity, and calcium deposition were reduced by 30%–50% on micropit surfaces, depending on the age of the titanium. In contrast, 7-day-old hybrid surfaces maintained equivalent levels of bioactivity compared with the fresh surfaces. Both micropit and micro-nano-hybrid surfaces were superhydrophilic immediately after UV treatment. However, after 7 days, the micro-nano-hybrid surfaces became hydrorepellent, while the micropit surfaces remained hydrophilic. The sustained bioactivity levels of the micro-nano-hybrid surfaces were nullified by treating these surfaces with Cl- anions. A thin TiO2 coating on the micropit surface without the formation of nanonodules did not result in the prevention or alleviation of the time-dependent decrease in biological activity. In conclusion, the micro-nano-hybrid titanium surfaces may slow the rate of time-dependent degradation of titanium bioactivity after UV photofunctionalization compared with titanium surfaces with microtopography alone. This antibiological aging effect was largely regulated by its sustained electropositivity uniquely conferred in TiO2 nanonodules, and was independent of the degree of hydrophilicity. These results demonstrate the potential usefulness of these hybrid surfaces to effectively utilize the benefits of UV photofunctionalization and provide a model to explore the mechanisms underlying antibiological aging properties.Keywords: bone–titanium integration, nanonodule, super osseointegration, dental and orthopedic implants, nanotechnology